Dominance of endemics in the reef fish assemblages of the Hawaiian Archipelago. (23rd September 2020) - Friedlander, Alan M.; Donovan, Mary K.; DeMartini, Edward E.; Bowen, Brian W.
Abstract: Aim: Species ranges provide a valuable foundation for resolving biogeographical regions, evolutionary processes and extinction risks. To inform conservation priorities, here we develop the first bioregionalization based on reef fish abundance of the Hawaiian Archipelago, which spans nearly 10° of latitude across 2, 400 km, including 8 high volcanic islands in the populated main Hawaiian Islands (MHI), and 10 low islands (atolls, shoals and islets) in the remote northwestern Hawaiian Islands (NWHI). Location: The Hawaiian Archipelago. Taxon: Fishes (276 taxa). Methods: We compiled 5, 316 visual fish surveys at depths of 1–30 m from throughout the Hawaiian Archipelago. Geographical range (km 2 ) for each species was measured as extent of occurrence (EOO) and area of occurrence (AOO). PERMANOVA and PCO were used to investigate drivers of fish assemblage structure. Distance‐based multivariate analyses were used to evaluate the relationship between fish assemblage structure and predictor variables including latitude, reef area, temperature, chlorophyll‐ a, wave energy and human population density. Results: Distinct fish assemblages exist in the MHI and NWHI, with two additional faunal breaks driven primarily by endemic species abundance. Latitude explained 37% of the variability in fish assemblages, with reef area accounting for an additional 9%. EOO showed a significant correlation with latitude. Endemics comprised 52%–55% of the numerical abundance at the northern end of the archipelago but only 17% on Hawai'i Island in the extreme south. Maximum size and activity regime (day vs. night) explained the most variation in the abundance of endemics. Main conclusions: The Hawaiian fish assemblages are strongly influenced by endemic species, affirming the archipelago as a biodiversity hotspot of high conservation value. The higher abundance of endemics in the NWHI may represent preadaptation to oceanic (oligotrophic) conditions. Resolution of distinct bioregions across the archipelago provides a better understanding of reef fish macroecology, with implications for management at the archipelago scale.